Assessing the bacterial and fungal functional diversity in soil and roots of common crops in Sapa district, Lao Cai province, Vietnam - Nguyen, Hung; Herrmann, Laetitia; Dung, Le Viet; Lesueur, Didier (2024)
The Sapa+ project aims to characterize the taxonomic and functional diversity of the soil microbiome associated with three crop types (rice, maize, and home garden) in two locations (Muong Hoa and Thanh Binh) in Sapa. The final goal is to determine significant biological differences across the microbiomes associated with these crops and locations as potential candidates for future in-depth studies (whether specific taxa, functions, or biomarkers). It should be noted that the experiment was only done for one season, so it cannot fully represent long-term correlations.